2017
DOI: 10.1038/nmeth.4325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computational methods for Hi-C data analysis

Abstract: Hi-C is a genome-wide sequencing technique to investigate the 3D chromatin conformation inside the nucleus. The most studied structures that can be identified from Hi-C - chromatin interactions and topologically associating domains (TADs) - require computational methods to analyze genome-wide contact probability maps. We quantitatively compared the performances of 13 algorithms for the analysis of Hi-C data from 6 landmark studies and simulations. The comparison revealed clear differences in the performances o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
355
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(390 citation statements)
references
References 41 publications
12
355
1
Order By: Relevance
“…Some ROIs are directly extracted by pattern recognition algorithms that work on interaction matrices [18]. In addition, other measures that are derived from different data types, such as protein-binding probability or gene expression, or existing metadata, such as genes or structural variants, are used to define ROIs too.…”
Section: Background—visual Analysis In Spatial Genome Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ROIs are directly extracted by pattern recognition algorithms that work on interaction matrices [18]. In addition, other measures that are derived from different data types, such as protein-binding probability or gene expression, or existing metadata, such as genes or structural variants, are used to define ROIs too.…”
Section: Background—visual Analysis In Spatial Genome Organizationmentioning
confidence: 99%
“…However, these algorithms can be very complex and often identify tens of thousands of specific pattern instances, many of questionable quality. Results of algorithms designed to identify the same type of pattern often differ substantially [18] and the lack of a ground-truth pattern collection hinders the evaluation of these algorithms. Thus, even if patterns can be retrieved automatically, assessing pattern quality requires human inspection.…”
Section: Introductionmentioning
confidence: 99%
“…The functional role for TADs and subTADs, and the extent to which they change across biological conditions, remains poorly understood, in part because of the paucity of methods for sensitive and accurate detection of sub-Mb-scale domains. Two recent comparative analyses reported that existing domain-calling methods accurately identify TADs but show poor ability to capture the full nested hierarchy of partially overlapping subTADs 11,12 . Thus, there is a great need for computational tools that accurately and sensitively detect the full nested hierarchy of chromatin domains across length scales.…”
mentioning
confidence: 99%
“…A/B compartments can readily be identified by using principal component analysis (PCA), since these compartments tend to be captured by the first principal component [20]. TADs can be mapped when interaction data is binned at 40 kb or less, using any one of a number of available algorithms (reviewed in [57] and [58]). Unlike chromosome territories, A/B compartments, or TADs, whose identification requires only moderate Hi-C data resolutions, chromatin loops can only be identified at much higher resolution (e.g., a 10 kb or higher resolution) [27].…”
Section: Identifying Architectural Features Of 3d Genome Organizationmentioning
confidence: 99%